Genetic Evaluation of Mitochondria Dysfunction in Coronary Artery Disease: Part 1 - Doğan, Nazlı; Çoban, Neslihan (Turk Kardiyoloji Dernegi arsivi : Turk Kardiyoloji Derneginin yayin organidir, 2023)
Mitochondria are cell organelles that play an important role in various cellular processes, especially in aerobic respiration and energy production. Although it has its own genome, the mitochondrial genome does not encode all of the proteins necessary for the mitochondria to function. Nuclear genome is needed for increased mitochondrial number, metabolic activities associated with mitochondria, and replication of mitochondrial deoxyribonucleic acid. As a result of mitochondria dysfunction in cells, oxidative stress occurs with the formation of reactive oxygen species, a product of oxidative metabolism, and the oxidant/antioxidant imbalance. Reactive oxygen species damage cellular molecules such as proteins, ribonucleic acid, deoxyribonucleic acid, and mitochondrial deoxyribonucleic acid under the conditions of oxidative stress. Molecular changes as a result of the reactive oxygen species cause the loss of mitochondria function, resulting in an increased number of dysfunctional mitochondria. Thus, the loss of function of mitochondria and defects in oxidative metabolism increase the formation of reactive oxygen species and cause an increase in mutations in mitochondrial deoxyribonucleic acid. These results also aﬀect mitochondrial biogenesis and accelerate the formation of multifactorial diseases as a result of the decrease in the number of functional mitochondria. In addition, microribonucleic acids, one of the epigenetic regulators, regulate nuclear and mitochondrial genes that control mitochondrial functions. Mitochondrial deoxyribonucleic acid mutated with reactive oxygen species, altered nuclear genome regulators and micro-ribonucleic acids, have been associated with various diseases mediated by mitochondrial dysfunction, including aging and coronary artery disease.